Inovasi pengembangan TPQ menjadi pusat studi tajwid menggunakan metode nasyid berbantuan articulate storyline - Siti Khoiruli Ummah; Safira Rahmadita Ismara; Devi Mellysapitri; L. Yasril Imam; Muhammad Natsir Hentihu (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
The aim of this article is to describe how implementing a mentoring program in e-tutorials in learning tajweed. Learning tajweed is done by the method nasheed where nasheed and the whole of the material tajweed put on the application of Articulate Storyline. The method of implementation of the program is done online using the help of Zoom for 10 meetings. As for the phases of the program starting with giving pretest then mentoring including socialization, pretest, training, post-test and evaluation. The target programs are masjeed tenager who will organize TPQ for future program. The results of the implementation of the program, namely the passage of the program according to the schedule. In addition, there is an increasing understanding of tajweed by 85% through the scores of pretest and posttest obtained. Testimonials partners very well, especially in terms of the practicality of the media, interest, and understanding. The sustainability of this program is learning tajweed online via Live Instagram assisted by ustadz.